2015
DOI: 10.1177/1934578x1501000669
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Biological Activity of Essential Oils from Wild Growing Aromatic Plant Species of Skimmia laureola and Juniperus macropoda from Western Himalaya

Abstract: The Himalayan region is very rich in a great variety of medicinal plants. In this investigation the essential oils of two selected species are described for their antimicrobial and larvicidal as well as biting deterrent activities. Additionally, the odors are characterized. Analyzed by simultaneous GC-MS and GC-FID, the essential oils' chemical compositions are given. The main components of Skimmia laureola oil were linalool and linalyl acetate whereas sabinene was found as the main compound for Juniperus macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…In recent years, reduced-risk agents such as essential oils and natural ("green") volatile compounds have gained increased recognition as key elements for improving integrated pest management strategies. 8,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Tanacetum annuum L. (synonyms: Balsamita annua L., B. multifida Clemente, and Chrysanthemum annuum [L.] Fiori) is a member of the giant family of Asteraceae (Compositae). Members of the genus Tanacetum have been used for medicinal purposes for decades due to their wide range of pharmacological and chemical properties as well as excellent medicinal values.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, reduced-risk agents such as essential oils and natural ("green") volatile compounds have gained increased recognition as key elements for improving integrated pest management strategies. 8,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Tanacetum annuum L. (synonyms: Balsamita annua L., B. multifida Clemente, and Chrysanthemum annuum [L.] Fiori) is a member of the giant family of Asteraceae (Compositae). Members of the genus Tanacetum have been used for medicinal purposes for decades due to their wide range of pharmacological and chemical properties as well as excellent medicinal values.…”
mentioning
confidence: 99%
“…In recent years, reduced-risk agents such as essential oils and natural (“green”) volatile compounds have gained increased recognition as key elements for improving integrated pest management strategies. 8,13 -27…”
mentioning
confidence: 99%
“…The leaf essential oils of J. macropoda have shown wide variation in chemical composition. A sample of leaf oil from Chamba, Himachal Pradesh had sabinene (27.5%), cedrol (14.1%), and terpinen-4-ol (9.4%) as the major components [ 154 ]. This oil did show antifungal activity and mosquito larvicidal activity.…”
Section: The Genus Juniperusmentioning
confidence: 99%
“…(Rutaceae), while sabinene was the main component in Juniperus macropoda Boiss. (Cupressaceae) (Stappen et al 2015a). Similarly, chemical profiling of essential oils from two Lamiaceae family members from Western Himalaya showed that pinocarvone, cis-pinocamphone and β-pinene were the main components of Hyssopus officinalis L. oil, while citronellol was the main component in oil of Dracocephalum 1 3 284 Page 2 of 9 heterophyllum Benth.…”
Section: Introductionmentioning
confidence: 99%